Antibacterial Efficacy of Selected Herbal Plants against Common Pathogenic Bacteria (Tribhuvan University Journal of Microbiology, 2024)
Objectives: The purpose of this study was to ascertain the effectiveness of particular herbal plants as antibacterial agents.Methods:  Different herbal plants were collected from Asan Bazar, Kathmandu, then the samples were dried, reduced to a powder, and combined with the appropriate amounts of hexane, ethyl acetate, and methanol to produce the extract accordingly. To obtain the desired extract, filtration, incubation, and vaporization were used. Escherichia coli, Staphylococcus aureus, and Bacillus spp. were the three test organisms. The test organism was uniformly swabbed onto a Muller Hinton Agar (MHA) plate. With the use of a borer, agar wells were created on MHA plates. The extracts of about 0.1 ml were applied to those wells using sterile micro pipette, which were then incubated at 37°C for 24 hours. Each well’s zone of inhibition (ZOI) was evaluated in relation to test organisms. Using the dilution approach, the minimum inhibitory concentration (MIC) was determined.Results: Bacillus spp. were found to be significantly inhibited by ethyl acetate extract of Coriandrum sativum (Coriander) with a ZOI of 25 mm. The ZOI 14mm test revealed that ethyl acetate extract of C. sativum had minimum efficacy against E. coli. The methanolic extract of C. sativum was reported to have MICs of 1:16, 1:32, and 1:64 against S. aureus, Bacillus spp., and E. coli, respectively.Conclusion: C. sativum is the most effective herbal plant against common pathogenic bacteria. Ethyl acetate extract was found to be more effective when compared to methanolic and hexane extracts. To update its medicinal value, additional research on its antibacterial characteristics may be required.